Incidence and risk factors of phlebitis among adult patient s with peripheral intravenous catheter - Daud, Azlina; Mohamad, Fatimah; Sowtali, Siti Noorkhairina (2018)
The insertion of peripheral intravenous catheter (PIVC) is essential among hospitalized patients for treatment purposes. However, this procedure usually fails before the end of therapy due to many complications. Phlebitis is one of the common complication occurred. Therefore, this study was conducted to determine the incidence rate of phlebitis among patients with PIVC and identify the associated risk factors contributed to phlebitis. Methods: This study used observational study design which was conducted in one of the hospitals located in East Coast Malaysia (Kuantan, Pahang). There were 161 data collected among patients who had PIVC in medical, gynecology and orthopedic wards from September 2016 until December 2016. The incidence of phlebitis on patients were evaluated using modified Visual Infusion Phlebitis (VIP) score checklist adopted from Royal College of Nursing in 2010. Other information regarding PIVC also being collected through assessment of patients. The data were analyzed using descriptive statistics and Chi square test. Results: The incidence of phlebitis, was found out to be 32.3% (n=52). The associated factors that contributed to the incidence of phlebitis in this study were presence of chronic diseases. Conclusions: Overall, phlebitis was the most frequent reason for PIVC removal and complication in this study. This high incidence from the result indicated a worrying outcome, as it was greater than the percentage recommended by Infusion Nursing Society. This study demonstrated that patients with chronic diseases were most likely to develop phlebitis.